المفاهيم األولية النظرية- المدخل- الطريقة- األسلوب - Ainur Rofiq Sofa (Al-Fikru : Jurnal Pendidikan Dan Sains, 2020)
Abstract:Before discussing further about the methods in learning Arabic, it would be better if we first understand the theories, approaches, and techniques that we will use. In this paper discusses the initial understanding in learning Arabic which includes theories and their kinds, approaches and kinds, methods and kinds, and techniques for learning Arabic which are certainly in accordance with the learning to be used.Based on these explanations it can be concluded that in order to study Arabic previously we must know and understand the theories, approaches, methods, and techniques that we will use. Because all of that is interconnected in learning Arabic which we will give. And to get the appropriate technique we must use the appropriate method and also the approach and theory so that we get maximum results.Keywords: theories, approaches, and techniques